Mafhum al Hashr wa Atharahu fi Ikhtilaf al Fuqoha - Mohammad Abdallah, Abuobaida (ADP Publisher, 2025)
The Concept of (AL-Hasr) Restriction and Its Impact on Juristic Disagreement. This study deals with the concept of exclusion and its impact in the difference of jurists, where the study aimed: to define the concept of exclusion, its images, arguments, jurisprudence implications in it, and the validity of it in some issues of worship, transactions, personal circumstances and crimes. The researcher therein followed the inductive, analytical, and comparative approach. The researcher concludes that exclusion is the concept of exclusion is: giving judgment to the object and being exposed to its negation beyond it; Because all the definitions mentioned above defined the types without limiting them all, just as the definition of the al-Qarafi proved the opposite of the judgment of the speaker of the Muscovite. He recommended researchers pay attention to studying word detectives; Because the orbit of extrapolating judgments on it. And that the concept of exclusion needs further research and studies and the extraction of jurisprudence branches that are based on the dispute in it.